1970
DOI: 10.22374/cjgim.v11i2.146
|View full text |Cite
|
Sign up to set email alerts
|

Resident-driven Quality Improvement Pre-post Intervention Targeting Reduction of Emergency Department Decision to Admit Time

Abstract: Long Emergency Department (ED) wait times represent a key point for quality improvement in many healthcare systems. A delayed ED disposition decision may lead to increased length of hospital stay, healthcare cost, and mortality. The objective of this resident-driven quality improvement (QI) intervention was to determine if a standardized resident admission protocol could reduce the ‘decision-to-admit’ (DTA) time of patients being assessed for admission to internal medicine (IM) at 3 tertiary care teaching hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Two studies reported on cost savings by reducing the consultation to decision time. 22,23 Interventions with the highest effectiveness judging by the magnitude of consultation to decision time achieved include SMS messaging, 16,18 direct consultation to senior physicians, 24 standardization of the admission protocol, 21,22 and education with audit and feedback. 19 Among these, education with audit and feedback was the most rigorously studied but also required the greatest amount of resources, including regular education sessions and feedback for trainees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported on cost savings by reducing the consultation to decision time. 22,23 Interventions with the highest effectiveness judging by the magnitude of consultation to decision time achieved include SMS messaging, 16,18 direct consultation to senior physicians, 24 standardization of the admission protocol, 21,22 and education with audit and feedback. 19 Among these, education with audit and feedback was the most rigorously studied but also required the greatest amount of resources, including regular education sessions and feedback for trainees.…”
Section: Discussionmentioning
confidence: 99%
“…Kachra et al introduced a standardized admission protocol to the general internal medicine service. 22 This protocol encouraged senior residents to make a disposition decision and enter admission orders within 2 hours of receiving a consultation request, without waiting for a junior resident to first complete the assessment. A reminder about utilization of the standardized protocol and summary data on consultation to decision time was emailed every 6 weeks.…”
Section: Standardization Of the Admission Processmentioning
confidence: 99%